EFEKTIVITAS DEKOMPOSER DAN KONSENTRASI PUPUK ORGANIK CAIR LIMBAH KUBIS PADA TANAMAN SELADA (Lactuca sativa L.) - Raden Arya Laksamana Yudha; Usman Siswanto; Putri Laeshita (JURNAL VIGOR, 2022)
This research was conducted to determine the effectiveness of the type of decomposer and liquid organic fertilizer concentration of cabbage waste material on the growth and yield of lettuce This experiment was arranged in bifactorial randomized block design arranged with three replications. The first factor was the type of cabbage waste material of liquid organic fertilizer decomposer consisting of control, Thiobacillus sp., indigenous microorganisms (IMO), and Effective Microorganisme-4. The second factor was the difference in liquid organic fertilizer concentrations of cabbage waste material consisting of 10 mL/L, 20 mL/L, and 30 mL/L. The observed variables included the number of leaves, leaf length, leaf fresh weight, leaf dry weight, root fresh weight, root dry weight, and root length. No significant difference was found with the application of liquid organic fertilizer with a type of decomposer and concentration of cabbage waste material on the whole observed variables. The application liquid organic fertilizer concentration of cabbage waste material waste did not respond to the growth and yield of lettuce plants on the parameters of the number of leaves, leaf length, leaf fresh weight, leaf dry weight, root fresh weight, root dry weight and root length. There was no interaction between the type decomposer and the liquid organic fertilizer of cabbage waste material on the growth and yield of lettuce. Based on the results of the research that has been carried out, it can be suggested that further research is needed on the length of the fermentation process in liquid organic fertilizer of cabbage waste material.